2020
DOI: 10.1029/2019jb018117
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Lateral Moho Variations Across the SE Tibetan Margin and Their Implications for Plateau Growth

Abstract: The tectonic uplift of the Tibetan Plateau is a focus in the geosciences. Middle‐lower crustal flow is a popular model to interpret the geodynamic mechanism on the margin of the Tibetan Plateau. The model predicts different surface and Moho topographies across the plateau boundary due to the different strengths of the surrounding blocks, that is, sharp boundaries on the eastern plateau boundary and gentle variations in the southeastern plateau boundary. Here, we employ receiver function and common conversion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In contrast, recent high-resolution P wave anisotropic tomography found that the fast orientation is parallel to the plateau margin as well as the contour lines of the relief and Moho depths [Huang et al, 2018;Han et al, 2020;. These results would indicate that crustal flow has been blocked by the strong Yangtze and Indochina crustal blocks [Huang et al, 2018;Xu et al, 2020].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, recent high-resolution P wave anisotropic tomography found that the fast orientation is parallel to the plateau margin as well as the contour lines of the relief and Moho depths [Huang et al, 2018;Han et al, 2020;. These results would indicate that crustal flow has been blocked by the strong Yangtze and Indochina crustal blocks [Huang et al, 2018;Xu et al, 2020].…”
Section: Introductionmentioning
confidence: 83%
“…Many seismological studies have been conducted to reveal the deep architecture of the SE Tibetan Plateau. The crustal thickness decreases from more than 60 km in eastern Tibet to 30 km in the surrounding Yangtze and Indochina blocks to the southeast [Wang et al, 2017;Xu et al, 2020]. Seismic velocities in the mid-lower crust beneath the plateau are generally lower than those in the surrounding regions [Yao et al, 2010;Liu et al, 2014;Bao et al, 2015b].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when seismic stations situate above a relatively complex crust, the Moho‐related multiples could be mingled with other intracrust‐generated signals, resulting in ambiguity in the estimation of Moho depth and bulk velocity ratio (Figure S8 in Supporting Information S1). In this study, to account for crustal velocity heterogeneities, we first construct the Moho geometry beneath southern California in the 3D community velocity model CVM‐S4.26 (Lee et al., 2014; hereafter referred to as the CVM‐S model) by applying the common conversion point (CCP) stacking technique (Zhu, 2000; Xu et al., 2020) to P‐wave RFs. We call the Moho geometry constrained by the Ps data as the Ps Moho.…”
Section: Constructing the Moho Geometry Using The Ps And Pmp Datamentioning
confidence: 99%
“…The locations of those discontinuities can be determined by migration techniques. In this study, we use the common conversion point (CCP) stacking method to image the Moho discontinuity (Zhu, 2000; Xu et al., 2020). The success of CCP stacking relies on the accuracy of the velocity model in which the time‐to‐depth mapping is performed.…”
Section: Constructing the Moho Geometry Using The Ps And Pmp Datamentioning
confidence: 99%